On farm interventions to minimise Campylobacter spp. contamination in chicken. Issue 1 (2nd January 2021) - Lu, T.; Marmion, M.; Ferone, M.; Wall, P.; Scannell, A. G. M.
ABSTRACT: 1. This review explores current and proposed on-farm interventions and assess the potential of these interventions against Campylobacter spp. 2. Interventions such as vaccination, feed/water-additives and, most importantly, consistent biosecurity, exhibit potential for the effective control of this pathogen and its dissemination within the food chain. 3. Due to the extensive diversity in the Campylobacter spp. genome and surface-expressed proteins, vaccination of poultry is not yet regarded as a completely effective strategy. 4. The acidification of drinking water through the addition of organic acids has been reported to decrease the risk of Campylobacter spp. colonisation in broiler flocks. Whilst this treatment alone will not completely protect birds, use of water acidification in combination with in-feed measures to further reduce the level of Campylobacter spp. colonisation in poultry may be an option meriting further exploration. 5. The use of varied types of feed supplements to reduce the intestinal population and shedding rate of Campylobacter spp. in poultry is an area of growing interest in the poultry industry. Such supplements include pro – and pre-biotics, organic acids, bacteriocins and bacteriophage, which may be added to feed and water. 6. From the literature, it is clear that a distinct, albeit not unexpected, difference between the performance of in-feed interventions exists when examined in vitro compared to those determined in in vivo studies. It is much more likely that pooling some of the discussed approaches in the in-feed tool kit will provide an answer. 7. Whilst on-farm biosecurity is essential to maintain a healthy flock and reduce disease transmission, even the most stringent biosecurity measures may not have sufficient, consistent and predictable effects in controlling Campylobacter spp. Furthermore, the combination of varied dietary approaches and improved biosecurity measures may synergistically improve control.